2020
DOI: 10.3390/en13184723
|View full text |Cite
|
Sign up to set email alerts
|

Development of Brushless Claw Pole Electrical Excitation and Combined Permanent Magnet Hybrid Excitation Generator for Vehicles

Abstract: Aiming at the problems of large excitation loss and low power generation efficiency of silicon rectifier generators and the unstable output voltage of permanent magnet (PM) generators, a hybrid excitation generator (HEG) with suspended brushless claw pole electrical excitation rotor (EER) and combined magnetic pole PM rotor is proposed in the present work. With only one fractional slot winding stator, the generator adopts PM field as the main magnetic field and electrical excitation field as the auxiliary magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…rough reading the above references, the author found that combined PMGs have strong magnetization ability and high air gap magnetic density [22,[26][27][28]. In addition, the brushless EEGs have good air gap field adjustment ability and high reliability [29][30][31].…”
Section: Introductionmentioning
confidence: 92%
“…rough reading the above references, the author found that combined PMGs have strong magnetization ability and high air gap magnetic density [22,[26][27][28]. In addition, the brushless EEGs have good air gap field adjustment ability and high reliability [29][30][31].…”
Section: Introductionmentioning
confidence: 92%
“…The comparison of different structures of hybrid excited electrical machines is very difficult because of their variety. They can be compared, e.g., in terms of their external characteristics (mechanical design) [1][2][3]21]. Hybrid excited electrical machines can also be categorized according to the path-determining design of the combined excitation flux.…”
Section: Review Of Hybrid Excited Machinesmentioning
confidence: 99%
“…However, it is difficult to regulate voltage and is easily affected by temperature. Hence, the hybrid excitation method is introduced as a decent candidate for the EV system [13][14][15]. In a hybrid excitation claw pole machine (HE-CPM), the PM excitation can bring high power density and the field excitation ensures good flux regulation capability [16,17].…”
Section: Introductionmentioning
confidence: 99%